Expressway Transportation Hub and Land Spatial Composite Utilization - An, Xinyang (Journal of Theory and Practice of Management Science, 2024)
This article mainly takes a domestic renovation project as an example to analyze its regional status, propose the main strategies for land spatial composite utilization, and list the relevant project planning processes. The construction and improvement of the highway network is a product of social industrialization and urbanization development. Land resources are non renewable resources. Land conservation is a major strategic issue related to the development of the entire national economy and social stability. The per capita land area in China is only one-third of the world's per capita, and the per capita arable land area is less than 43% of the world's per capita. Under the macro control policy of land tightening implemented by the country, the rational and economical use of land is related to the sustainable development of highway construction. Among them, interchanges have obvious characteristics of centralized and high consumption in terms of land occupation, making them a "major user" of land for the construction of highway sub projects. The rational use of land is an important link in saving land for highway construction, which is worth studying and exploring.